Translate the phrase into an algebraic expression.
3 times b

Answers

Answer 1
Answer:

Answer:

3b

Step-by-step explanation:

It`s just . . . 3b lol

When numbers and variables multiply, they are put in the form of (integer)(variable). They phrase can only be further simplified if there is a number substitution for b.


Related Questions

What are the prime numbers of numbers 1-49?
Which word or phrase best clarifies the relationship between the claim andthe evidence?Owning your own business can allow you more freedom than a typicaljob. ______you may be able to schedule your work around other pursuits.A meanwhileB the first reason C for example D actually
Need rn! worth 30Evaluate the function T(x)=19−x, when x=−3.a.) 57b.) 22c.) 16d.) −16
3/10 off the normal price 400
In the clip from the Simpsons, Ralph charges Bart twice the fair from Tucson to Flagstaff, minus 2/3 the fair from Albuquerque to El Paso. It costs $40 to travel from Tucson to Flagstaff, and $90 to travel from Albuquerque to El Paso. So, how much does Bart need to pay?

Which numbers are a distance of 5 units from 3 on the number line?Write your answer : ___ and ___

Answers

3 + 5 = 8

3 - 5 = -2

-2 and 8

Question 3! How to do it?

Answers

Hello,

x/6=tan 60°==>x/6=√3==>x=6√3

Answer B

The radius of a sphere is 6 centimeters. Which is the volume of the sphere?

Answers

the answer is in the file below
it simplifies to 288π or 904.78cm
Volume=4/3•pi•radius^3
=4/3•pi•6^3
=905cm^3 ( 3significant figures )

What is the volume enclosed by the slanted prism in the diagram 12 cm 9 cm area of base = 25 cm

Answers

V=Bh V = volume B = area of the base h = height* *The height is the perpendicular height, 9 cm in this case, not the slant length, 12 cm. 

so its  225cm

hope it helped

I WILL GIVE BRAINLIEST:)) Use the table to find the products of the two polynomials. Write your answer in descending order.

Answers

Answer:

A) 4x^(4)-4x^(3)-16x^(2)+16x

B)4x^(4)-4x^(3)-16x^(2)+16x

Step-by-step explanation:

look at picture

What is the simplified expression for 2(x - 5)?

Answers

If you would like to know the simplified expression for 2 * (x - 5), you can find this using the following steps:

2 * (x - 5) = 2 * x - 2 * 5 = 2 * x - 10

The correct result would be 2 * x - 10.
The answer would be 2x-10